Cytotoxicity, antimicrobial and antioxidant activity of eight compounds isolated from Entada abyssinica (Fabaceae) - Dzoyem, Jean P. (BMC Res Notes, 2017)
BACKGROUND: Entada abyssinica is a plant traditionally used against gastrointestinal bacterial infections. Eight compounds including three flavonoids, three terpenoids, a monoglyceride and a phenolic compound isolated from E. abyssinica were investigated for their cytotoxicity, antibacterial and antioxidant activity. RESULTS: Compounds 7 and 2 had remarkable activity against Salmonella typhimurium with the lowest respective minimum inhibitory concentration (MIC) values of 1.56 and 3.12 µg/mL. The antioxidant assay gave IC(50) values varied from 0.48 to 2.87 μg/mL in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, from 2.53 to 17.04 μg/mL in the 2,2′-Azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) diammonium salt (ABTS) assay and from 1.43 to 103.98 µg/mL in the FRAP assay. Compounds had relatively low cytotoxicity (LC(50) values ranging from 22.42 to 80.55 µg/mL) towards Vero cells. Ursolic acid had the most potent cytotoxicity against THP-1 and RAW 264.7 cells with LC(50) values of 9.62 and 4.56 μg/mL respectively, and selectivity index values of 7.32 and 15.44 respectively. CONCLUSION: Our findings suggest that among the terpenoid and flavonoid compounds studied, entadanin (compound 7) possess tremendous antibacterial activity against S. typhimurium and could be developed for the treatment of bacterial diseases.